SOME NEW RESULTS FOR REICH TYPE MAPPINGS ON CONE b-METRIC SPACES OVER BANACH ALGEBRAS - Vujaković, Jelena; Auwalu, Abba; Šešum-Čavić, Vesna (Bulletin of Natural Sciences Research, 2018)
The main purpose of this paper is to present some fixed point results concerning the generalized Reich type α-admissible mappings in cone b-metric spaces over Banach algebras. Our results are significant extensions and generalizations of resent results of N. Hussain at al. (2017) and many well-known results in abundant literature. We also gave an example that confirmed our results.
Keywords: Cone b-metric space; Banach algebra; α-admissible mapping; α-regular; Fixed point; c-sequence